2011
DOI: 10.1016/j.alcohol.2010.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal ethanol exposure alters hypothalamic transforming growth factor-α and erbB1 receptor signaling in the female rat

Abstract: Glial derived transforming growth factor-α (TGFα) activates the erbB1/erbB2 receptor complex on adjacent glial cells in the medial basal hypothalamus (MBH). This receptor activation stimulates the synthesis and release of prostaglandin-E 2 (PGE 2 ) from the glial cells, which then induces the release of prepubertal luteinizing hormone releasing hormone (LHRH) secretion from nearby nerve terminals; thus, showing the importance of glial-neuronal communications at the time of puberty. Ethanol (EtOH) is known to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…This is in agreement with previous reports using this feeding regimen and showing similar animal weights and hormone levels, as well as gene and protein expressions between these two CON groups of prepubertal, growing animals [10, 17, 20]. Similarly, no differences were detected between the two diet-fed CON groups supplemented with Mn.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous reports using this feeding regimen and showing similar animal weights and hormone levels, as well as gene and protein expressions between these two CON groups of prepubertal, growing animals [10, 17, 20]. Similarly, no differences were detected between the two diet-fed CON groups supplemented with Mn.…”
Section: Resultssupporting
confidence: 93%
“…PGE 2 is a critical component in the glial regulation of LHRH secretion, since once it is released it binds to its receptor on nearby LHRH nerve terminals in the ME, causing the release of this peptide [33, 41, 45]. Because ALC can suppress both TGFα and PGE 2 secretions [20], we also investigated in this study whether Mn supplementation could antagonize the actions of ALC on PGE 2, synthesis since it represents a critical pathway to LHRH neuronal secretion [33, 41, 45]. In support of this rational, previous studies have indicated Mn supplementation can up-regulate COX 2 expression in vivo and can stimulate PGE 2 and LHRH release from MEs incubated in vitro [26].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results demonstrate the inhibitory effects of alcohol on the glial TGFα/erbB1 pathway contributing to the production and secretion of PGE 2 within the MBH, hence, indicating that this is one of the mechanisms by which alcohol suppresses PGE 2 and subsequently, LHRH secretion (Hiney & Dees, 1991; Lomniczi et al, 2000; Srivastava et al, 2011). The fact that alcohol can negatively affect the erbB1 receptor is important since it is known that an alteration in the function of this receptor is associated with delayed puberty (Apostolakis, Garai, Lohmann, Clark, & O’Malley, 2000).…”
Section: In Vitro and In Vivo Effects Of Alcohol On Erbb1 Receptor Acmentioning
confidence: 66%
“…Specifically, it was shown in immature female rats that short-term alcohol exposure via a liquid diet feeding regimen for 4 and 6 days caused an increase in hypothalamic TGFα gene and protein expressions. TGFα gene expression was increased markedly at 4 days and was still elevated after 6 days (see Srivastava et al, 2011). This effect paralleled the increased TGFα protein expressions on both days (Fig.…”
Section: In Vitro and In Vivo Effects Of Alcohol On Erbb1 Receptor Acmentioning
confidence: 98%
See 1 more Smart Citation